Analisis Kekuatan Struktur pada Gerbong Datar - Andreas, Teddy; Sukarnoto, Tono; Soeharsono, Soeharsono (MESIN, 2019)
The PPCW railroad flatcars is railroad flatcars used to transport container loads with a maximum load capacity of up to 42 tons. In its use, these railroad flatcars are used to transport the cement bags in the pallet arrangement resulting in crack in the bottom frame of the PPCW railroad flatcars structure. The purpose of this analysis is to find out stress value and deformation value that occurred in the railroad flatcars due to the cement bags loading. The analysis process begins with modeling according to the original size of the railroad flatcars which is then followed by providing the support, gravity, loads, and material specifications used. Based on the result of analysis that has been obtained from the load of cement bags of 546,000 N and ratchet lashing of 900,000 N on the frame of PPCW railroad flatcars, we obtained the maximum von Mises stress value of 231.91 MPa arising on the bottom frame of the PPCW railroad flatcars structure as the site of cracking and the maximum total deformation value of 19.526 mm arising in the center of the railroad flatcars. The PPCW railroad flatcars made from SS400 with yield strength value of 245 MPa. Therefore, it was found that the value of stress arising in the railroad flatcars is still in the safe area and is allowed.